(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
This research has been conducted through 2016-2017 in Latakia to determine the genetic relationship between twelve natural accessions that belongs to three wild Thymus species (Thymus syriacus, Thymus capitatus, Thymus sp.) from different geographical and bioclimatic zones in Latakia, using RAPD markers (Random amplified polymorphic DNA). Twelve oligonucleotide primers were screened, and among them, 10 primers showed clear polymorphic patterns between the studied species. A total number of 103 bands were detected from 10 RAPD primers, of which 81 were polymorphic (78.64%), with an average of 8.1 polymorphic bands per primer. The large proportions of genetic variation (50%) were observed within accessions from Aldaliah zone (Thymus sp.) and Solas zone (T. syriacus), while low proportions of genetic variation were observed within Solas and Kasab accessions (T. syriacus), Some primers such as OPTH-4 and OPAN-08 show high ability to detect genetic variation within the studied species. أجري البحث خلال عامي 2016-2017 في محافظة اللاذقية على 12 طرازاً تتبع لثلاثة أنواع من الزعتر Thymus syriacus, Thymus capitatus, Thymus sp.)) منتشرة في مناطق جغرافية متباينة من محافظة اللاذقية . تم استخدام تقنية الـ RAPD لتحديد القرابة الوراثية بين هذه الطرز. تم اختبار 12 بادئة عشوائية أظهرت 10 بادئات منها كفاءة عالية في كشف الاختلافات الوراثية بين الأنواع المدروسة أعطت البادئات العشر مجتمعةً 103 حزمة, منها 81 حزمة متباينة ( 78،64%) بمعدل (8،1) حزمة متباينة للبادئة الواحدة. بلغت أعلى نسبة من التباين ضمن شجرة القرابة الوراثية (50%) بين طرز النوع Thymus sp. المنتشرة في موقع الدالية مع طرز النوع T. syriacus المنتشرة في موقع سولاس, بينما بلغت هذه النسبة أدناها بين طرز النوع T. syriacus المنتشرة في موقعي سولاس وكسب, أظهرت بعض البادئات (OPTH-4, OPAN-08) كفاءة في كشف التباينات الوراثية بين الأنواع المدروسة.